2019
DOI: 10.3847/1538-3881/aaf725
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Dynamics and the Variable Transit of KELT-9 b*

Abstract: We present a spectrally and temporally resolved detection of the optical Mg I triplet at 7.8σ in the extended atmosphere of the ultra-hot Jupiter KELT-9 b, adding to the list of detected metal species in the hottest gas giant currently known. Constraints are placed on the density and radial extent of the excited hydrogen envelope using simultaneous observations of Hα and Hβ under the assumption of a spherically symmetric atmosphere. We find that planetary rotational broadening of v rot = 8.2 +0.6 −0.7 km s −1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
187
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(208 citation statements)
references
References 92 publications
20
187
1
Order By: Relevance
“…Moreover, Hoeijmakers et al (2018Hoeijmakers et al ( , 2019 reported the detection of Cr ii, Fe i, Fe ii, Mg ii, Na i, Sc ii, Ti ii and Y ii, as well as evidence of Ca i, Cr i, Co i and Sr ii in its atmosphere. Additionally Cauley et al (2019) detected in this planet H β and Mg i triplet. These atmospheric species have also been detected in the cooler UHJs WASP-18b (Arcangeli et al 2018), WASP-33b (von Essen et al 2018), WASP-12b (Jensen et al 2012), WASP-76b (Seidel et al 2019) and MASCARA-2b (Casasayas-Barris et al 2018.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Moreover, Hoeijmakers et al (2018Hoeijmakers et al ( , 2019 reported the detection of Cr ii, Fe i, Fe ii, Mg ii, Na i, Sc ii, Ti ii and Y ii, as well as evidence of Ca i, Cr i, Co i and Sr ii in its atmosphere. Additionally Cauley et al (2019) detected in this planet H β and Mg i triplet. These atmospheric species have also been detected in the cooler UHJs WASP-18b (Arcangeli et al 2018), WASP-33b (von Essen et al 2018), WASP-12b (Jensen et al 2012), WASP-76b (Seidel et al 2019) and MASCARA-2b (Casasayas-Barris et al 2018.…”
Section: Introductionmentioning
confidence: 62%
“…Fe I and Fe II have been previously detected in the atmosphere of KELT-9b by Hoeijmakers et al (2018Hoeijmakers et al ( , 2019 using the cross-correlation method and by Cauley et al (2019) using transmission spectroscopy. KELT-9b, however, has an extremely high day-side equilibrium temperature (T eq = 3920 K), while MASCARA-2b's is much lower (T eq = 2260 K).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Yan & Henning (2018) reported an extended hydrogen atmosphere (∼ 1.64 R p ) using Hα observations with the CARMENES spectrograph. The Hα detetion was confirmed by Cauley et al (2019), who observed variability in the in-transit absorption light curve suggesting that the transiting gas is not uniform. Using high-resolution optical spectra from HARPS-N during four separate KELT-9b transits Borsa et al (2019) observed the atmospheric Rossiter-McLaughlin effect.…”
Section: Introductionmentioning
confidence: 85%
“…For Hα, we have measured a line FWHM of 15.4 km s −1 , i.e., σ = FWHM/2.355 = 6.5 km s −1 . Assuming that Hα originates in a similar layer to the Na doublet and that its line width is set by thermal broadening and the maximum optical depth at line center, based on the equations (3) and (4) In addition to WASP-52b, five other planets have simultaneous detections of Na and Hα, including HD 189733b Jensen et al 2012;Cauley et al 2015Cauley et al , 2016Huang et al 2017), KELT-20b (Casasayas-Barris et al 2019), KELT-9b (Yan & Henning 2018;Cauley et al 2019), WASP-12b (Jensen et al 2018). and WASP-121b (Cabot et al 2020).…”
Section: The Atmosphere Of Wasp-52bmentioning
confidence: 99%